Erratum: Effect of Non-Covalent Self-Dimerization on the Spectroscopic and Electrochemical Properties of Mixed Cu(I) Complexes (Rsc Adv. 2023 13 (825-838) Doi: 10.1039/D2ra05341a) - Costamagna-Martra, J; Costamagna-Martra, J; Guerrero-Nunez, J; Guerrero-Nunez, J; Lemus-Chavez, L; Lemus-Chavez, L; Vera-Oyarce, C; Vera-Oyarce, C; Silva-Molina, C; Silva-Molina, C; Martinez-Gomez, F; Caceres-Vasquez, J (Royal Society of Chemistry, 2023)
The authors regret that the funding information was incorrectly shown in the Acknowledgements section of the original manuscript. The corrected funding acknowledgement is as shown below. The authors acknowledge the support of DICYT-USACH, FONDECYT 1191902, and FONDEQUIP-EQM 150106. C. V. acknowledges support from postdoctoral grant FONDECYT 3170661, J. C.-V. acknowledges a CONICYT Doctoral Fellowship 21141067. The Royal Society of Chemistry apologises for these errors and any consequent inconvenience to authors and readers. © 2023 The Royal Society of Chemistry.